2019
DOI: 10.1007/s40333-019-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Flow regime changes in three catchments with different landforms following ecological restoration in the Chinese Loess Plateau

Abstract: The Chinese Loess Plateau is known as one of the most severe soil erosion regions in the world. Two ecological restoration projects, i.e., the integrated soil conservation project since the 1970s and the ''Grain for Green'' project since 1999, have been progressively implemented to control the soil erosion in this area. Ecological restoration has greatly changed flow regime over the past five decades. However, the mechanism of how flow regime responds to ecological restoration among landforms remains poorly un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…To address devastating land degradation and soil erosion, the Chinese government has launched a series of ecological engineering programs for environmental restoration and protection [8]. Many studies have shown that these programs have helped to increase vegetation cover and improve ecosystem services [9][10][11]. However, their environmental effects have not yet been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…To address devastating land degradation and soil erosion, the Chinese government has launched a series of ecological engineering programs for environmental restoration and protection [8]. Many studies have shown that these programs have helped to increase vegetation cover and improve ecosystem services [9][10][11]. However, their environmental effects have not yet been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%